New Zealand : Financial Sector Assessment Program: Detailed Assessment of Observance-Insurance Core Principles. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This paper presents an assessment of the Observance of Insurance Core Principles in New Zealand. Observance of these principles in New Zealand falls significantly short. In some areas, the implementation of initiatives that would improve observance is incomplete. Supervisory risk assessment and enhancement of regulatory reporting by insurers are limited, which compromises effective off-site supervision, macroprudential analysis, and publication of aggregate information on the market. The Reserve Bank of New Zealand should focus in regulation and supervisory work on setting standards on corporate governance, risk management, and internal controls. It should assess risk in these areas to promote the effectiveness of insurers' governance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet